Characterisation of 11 Microsatellite DNA Markers from the Neotropic Cormorant (Phalacrocorax Brasilianus). (February 2017) - Rodrigues, Pedro; Micael, Joana; Hernandez, Carlos; Verdugo, Claudio
The advances of molecular techniques have increased the development of cost and time-effective libraries of molecular markers, such as microsatellites, which allow us to estimate genetic parameters in order to characterise species' population structures. The Neotropic Cormorant ( Phalacrocorax brasilianus ) is one of the most abundant and widespread seabirds from the American continent, being present in a wide range of habitats, however further information about genetic markers in this species is scarce. A total of 26 pairs of primers were synthesised and 22 microsatellites were amplified correctly; 11 of them were polymorphic. The number of alleles per locus ranged from three to seven with a mean of 4.6 per locus. Six loci showed significant departure from Hardy–Weinberg equilibrium. The microsatellite markers identified and characterised in the present study are the first set developed for P. brasilianus and will contribute to the genetic map, quantitative traits mapping, and phylogenetic analysis of this species.